DETEKSI DINI KESEHATAN JIWA PERAWAT DAN PENERAPAN ADAPTASI KEBIASAAN BARU PADA MASA PANDEMI COVID-19 DI PROVINSI ACEH - Hasniah Hasniah; Putro Simeulu; Munazar Munazar; Arbaiyah Arbaiyah (Poltekkes Kemenkes Aceh, 2023)
Stress that arises as a result of the Covid-19 pandemic can be in the form of fear and anxiety about personal health and the health of other loved ones, changes in sleep patterns and or eating patterns, difficulty sleeping and concentrating, and aggravating the condition of someone who has a history of chronic illness and/or psychological disorders. The purpose of this study was to find out the results of early detection of mental health by nurses and the application of New Habit Adaptation during the Covid-19 pandemic in Aceh Province. This research method uses a survey research method, with a descriptive research design using a questionnaire as a data collection instrument. The results of the study of 120 respondents obtained the results of the detection of mental health by nurses: 12 respondents who were detected to have Neurosis (10%) and suicidal thoughts/ideas 1 person (0.83%). While the results of the Implementation of New Habit Adaptation (IMR) in nurses showed an increase in physical immunity by 40%, an increase in mental immunity was carried out on average by 38.3%, prevention of transmission of Covid-19 had an average value of 30.1%, and prevention of mental health problems related to Covid -19 by 28.4%. Overall, it can be concluded that the results of early detection of mental health by nurses during the Covid-19 pandemic showed healthy results (no one experienced psychotic disorders and only a small percentage of 10% had neurotic disorders).